PENGARUH TINGKAT LITERASI KEUANGAN SYARIAH TERHADAP KINERJA USAHA MIKRO KECIL DAN MENENGAH DI KOTA BANDA ACEH - Evriyenni Evriyenni (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
Financial literacy is one of the success factors for the economy and the welfare of the people in Indonesia. The low level of financial literacy has an impact on people's economic growth, including Micro, Small and Medium Enterprises (MSMEs). Aceh is one of the regions in Indonesia that implements Islamic sharia, including the activities of its financial institutions. Therefore, it is important for MSME actors in Aceh to have a good level of Islamic financial literacy. This study aims to examine the effect of the dimensions of Islamic financial literacy which includes financial knowledge, financial attitudes and financial capabilities on the financial performance of MSMEs. The research population includes 927 MSMEs in Syiah Kuala District, Banda Aceh City. While the research sample was 90 SMEs based on the Slovin formula with simple random sampling technique. The data used are questionnaires obtained from MSME actors with documentation techniques. Data were analyzed using linear regression method. The results of the study indicate that both separately and together, the dimensions of Islamic financial literacy, namely financial knowledge, financial attitudes and financial capabilities affect the financial performance of MSMEs in Syiah Kuala District, Banda Aceh City